Evaluate the expression for p = 2, q = 4.9, and r = 3.5.

Write your answer as a decimal or whole number.

pqr

9 answers

To evaluate the expression \( pqr \) given the values \( p = 2 \), \( q = 4.9 \), and \( r = 3.5 \), we simply multiply the three numbers together:

\[ pqr = 2 \times 4.9 \times 3.5 \]

First, we calculate \( 2 \times 4.9 \):

\[ 2 \times 4.9 = 9.8 \]

Next, we multiply the result by \( 3.5 \):

\[ 9.8 \times 3.5 = 34.3 \]

Thus, \( pqr = 34.3 \).

The final answer is:

\[ \boxed{34.3} \]

Evaluate the expression for h = –1.4, j = –17, and k = –14.8.

Write your answer as a decimal or whole number.

hj − j + k =

To evaluate the expression \( hj - j + k \) with the given values \( h = -1.4 \), \( j = -17 \), and \( k = -14.8 \), we will calculate each part step by step.

  1. Calculate \( hj \): \[ hj = (-1.4) \times (-17) = 23.8 \]

  2. Now substitute this result into the expression: \[ hj - j + k = 23.8 - (-17) + (-14.8) \]

  3. Simplify \( -(-17) \) to \( +17 \): \[ = 23.8 + 17 - 14.8 \]

  4. Next, calculate \( 23.8 + 17 \): \[ = 40.8 \]

  5. Finally, subtract \( 14.8 \) from \( 40.8 \): \[ 40.8 - 14.8 = 26 \]

Thus, the final answer is:

\[ \boxed{26} \]

Evaluate the expression for g = –3.8 and h = 3.

Write your answer as a decimal or whole number.

gh2 − 1 =

To evaluate the expression \( gh^2 - 1 \) with the given values \( g = -3.8 \) and \( h = 3 \), we will proceed step by step.

  1. Calculate \( h^2 \): \[ h^2 = 3^2 = 9 \]

  2. Now substitute \( h^2 \) into the expression: \[ gh^2 - 1 = g \cdot 9 - 1 \]

  3. Substitute \( g = -3.8 \): \[ = -3.8 \cdot 9 - 1 \]

  4. Calculate \( -3.8 \cdot 9 \): \[ -3.8 \cdot 9 = -34.2 \]

  5. Finally, subtract 1: \[ -34.2 - 1 = -35.2 \]

Thus, the final answer is:

\[ \boxed{-35.2} \]

Evaluate the expression for j = –5 and k = –1.9.

Write your answer as a decimal or whole number.

j2k + k =

To evaluate the expression \( j^2k + k \) with the given values \( j = -5 \) and \( k = -1.9 \), we will follow these steps:

  1. Calculate \( j^2 \): \[ j^2 = (-5)^2 = 25 \]

  2. Now substitute \( j^2 \) into the expression: \[ j^2k + k = 25k + k \]

  3. Combine the terms: \[ = 25k + k = 26k \]

  4. Substitute \( k = -1.9 \): \[ = 26 \times (-1.9) \]

  5. Perform the multiplication: \[ 26 \times (-1.9) = -49.4 \]

Thus, the final answer is:

\[ \boxed{-49.4} \]

Evaluate the expression for v = 5, w = –1.3, and x = –14.3.

Write your answer as a decimal or whole number.

vw2 − x =

To evaluate the expression \( vw^2 - x \) with the given values \( v = 5 \), \( w = -1.3 \), and \( x = -14.3 \), we will follow these steps:

  1. Calculate \( w^2 \): \[ w^2 = (-1.3)^2 = 1.69 \]

  2. Now substitute \( w^2 \) into the expression: \[ vw^2 - x = v \cdot w^2 - x \] Substituting \( v = 5 \) and \( w^2 = 1.69 \): \[ = 5 \cdot 1.69 - x \]

  3. Calculate \( 5 \cdot 1.69 \): \[ 5 \cdot 1.69 = 8.45 \]

  4. Now substitute \( x = -14.3 \): \[ = 8.45 - (-14.3) \]

  5. Simplify the expression: \[ = 8.45 + 14.3 = 22.75 \]

Thus, the final answer is:

\[ \boxed{22.75} \]